Hubungan dukungan keluarga dengan depresi pada lansia di Panti Sosial Werdha Wana Seraya Denpasar Bali - Nataswari, Putu Pradnyadewi; Ardani, IGA Indah (E-Jurnal Medika Udayana; Vol 7 No 2 (2018): E-Jurnal Medika Udayana, 2018)
Depression is a disease that often occurs in the elderly. There are several factors that influence the occurrence of depression in the elderly, one of which is the presence of family support. This study was conducted to determine the relationship between family support with depression in the elderly in Elderly Social Institution Wana Seraya Denpasar Bali. This study used an analytical technique using cross-sectional sampling technique by total sampling. This study used two types of analysis, univariate analysis to determine the frequency distribution of each variable and bivariate analysis to determine the relationship between the two variables. Of the total 40 samples, a total of 35 respondents (87.5%) had a good family support, and as many as five respondents (12.5%) of respondents had poor family support. A total of 21 respondents (52.5%) experienced depression and as many as 19 respondents (47.5%) did not have depression. From the results of the bivariate analysis p value = 0.65 which indicates that there was no significant relationship between family support with depression in the elderly in Elderly Social Institution Wana Seraya Denpasar Bali, but the OR value obtained was 1.7, which suggests that depression happens to the respondent with the support of poor families increased 1.7 times compared with good family support. This suggests that family support is a risk factor for depression in the elderly in Elderly Social Institution Wana Seraya Denpasar Bali. Keywords: family support, depression, elderly